WaNuLCAS modelling of runoff and soil loss for different agroforestry scenarios in a catchment in Northern Vietnam - Nolin, Lina (2006)
A large part of the world arable land is affected by degradation and a global population pressure drivespeople to unsustainable cultivation methods to meet food demands. Water is the most common cause of erosion and soil erosion tends to be especially severe in steep lands in areas with monsoon rains. Agroforestry, meaning plantation of trees in combination with crops, is considered to be a promising approach to sustainable land use because it can meet the demands of food at the same time as of the need of soil and water conservation.